Power Extraction from an Oscillating Water Column; Experimental Setup and Preliminary Results - Gionet-Gonzales, Julia; Koola, Paul M.; Girimaji, Sharath S. (OCEANS 2023 - MTS/IEEE U.S. Gulf Coast, 2023)
The need for alternative energy sources is at an all-time high due to the increased awareness of climate-related issues. Wave energy utilizing the transient ocean waves is a promising solution as around 40% of the U.S. population resides in counties along the coast, putting extra strain on those areas. The oscillating water column (OWC) is a well-known wave energy converter (WEC) that has been the subject of many research studies. The development of an accurately scaled model is important in designing WECs to determine which characteristics best suit wave conditions at the target location. Recent studies have shown that air compressibility plays a larger role in scaling the model to full scale than previously assumed. The effect caused by the air-water energy exchange is analyzed in these experiments and compared with conventional air chamber models and compressed external air volumes. It was confirmed that air compressibility plays an important role in the effectiveness of OWCs. This work will enable us to correctly match a turbogenerator, the power take-off at full scale.